Chemical Composition and Antimicrobial Activity of Artemisia annua L. Essential Oil from Iran - MR Verdian-rizi; E Sadat-Ebrahimi; A Hadjiakhoondi; MR Fazeli; M Pirali Hamedani (Institue of Medicinal Plants, ACECR, 2008)
The composition of the essential oil obtained from the dried flowering aerial parts of Artemisia annua L. (Compositae) was analysed by GC and GC/MS. Thirty-two components were identified in the essential oil of A. annua L. with campher (48.00%), 1,8-cineole (9.39%), camphene (6.98%) and spathulenol (4.89%) as major components. The essential oil was evaluated for antibacterial and antifungal activities. The activity was more pronounced against fungal organisms than against Gram-positive and Gram-negative bacteria.